Examination of the catalytic reduction of NO by CH₄ in a Pt—polybenzimidazole membrane—Pt system with and without polarization - Bandur, V.A.; Petrushina, I.M.; Refshauge, R.; Bjerrum, N.J. (Украинский химический журнал, 2005)
The catalytic reduction of NO by methane was studied using a Pt—polybenzimidazole membrane—Pt system with and without polarization at 135 °C. It was concluded that a hydrogen counter electrode probably will be more useful in connection with electrochemical promotion of re-examined catalytic reactions.